Mengajarkan Keterampilan Abad 21 4C (Communication, Collaboration, Critical Thinking and Problem Solving, Creativity and Innovation) di Sekolah Dasar - Slamet Widodo; Rizky Kusuma Wardani (MODELING: Jurnal Program Studi PGMI, 2020)
Nowadays, teaching primary students grades in the 21st-century era is more challenging than ever for teachers. One of the challenges is the necessity of developing teaching 21st-centuries’ skills such as Communication, Collaboration, Critical Thinking, and Problem Solving, Creativity, and Innovation (henceforth, 4C). Those skills must be taught at all educational levels, especially at the primary school with considering some of aspects such as the students’ needs and students’ development, due to the students face the very fast-changing era periodically. Indirectly, the primary students are being part of 21st-century society. Based on the fact as mentioned, it was led the researchers to conduct this study. Therefore, the aim of this study is to describe 21st-century learning by integrating it for every grade student at the primary school level. Moreover, a literature review was chosen to be a research method of this study through 5 stages process, namely: 1) Determining the research theme; 2) Collecting the relevant articles; 3) Classifying the articles; d) Synthesizing articles and highlighting the important points; and 5) Writing research articles based on the synthesizing result. As a result, two conclusions were found, namely: 1) Teaching 21st-century skills can be done by teachers at all educational levels, and 2) Learning Process at 21st-century can be innovated by teachers with considering the appropriate materials, the students 'needs, and the students' learning conditions.